The Role of Religious Linguistics in John Hick’s “Philosophy of Religion” - yaser bakhshiyan; ali allah bedashti; abas izadpanah (̒Ilm-i Zabān, 2019)
Philosophy of religion is a new area of study in the field of epistemology. The topic of the language of religion, as one of the important branches of this science, is of particular importance. One of the current prominent philosophers of religion is John Hick. He extends Wiganstein’s “linguistic game” theory and the general interpretation of the “experience of the kind” to all areas of behavior and religious experiences to arrive at religious pluralism. In fact, Hick based his philosophy of religion on the language and thought boundaries of Wigtenstein and Kant. The important results obtained from John Hick’s method and principles and its extension to all domains makes research on it indispensable. Therefore, the present research study sought to explore and criticize the principles of John Hick’s philosophy of religion and the role of linguistics in the knowledge obtained. The key findings of the study are the existence of a superficial look in linguistics and the lack of belief in the definition of meaning in non-experimental sciences.